Real-World Effectiveness and Safety of Esketamine Nasal Spray in Treatment-Resistant Depression: A Retrospective Observational Study - Mostafa A. Sayed Ali; Palanisamy Amirthalingam; Hanan Alshareef; Mohammed Zayed Alassiry; Ahmed Samir Elshenawy; Sayed Hosam Eldin Mansour; Ahmed Aljabri (Healthcare, 2026)
Background/Objectives: This study evaluated the real-world effectiveness and safety of intranasal esketamine plus oral antidepressants compared with venlafaxine-based oral antidepressant therapy in adults with moderate-to-severe treatment-resistant depression (TRD). Methods: This retrospective cohort study used electronic medical records from a mental health hospital between January 2023 and December 2025. Adults with moderately severe or severe major depressive disorder who had not responded adequately to at least two antidepressant trials received esketamine plus oral antidepressants or venlafaxine-based therapy. The outcomes were changes in the Patient Health Questionnaire-9 (PHQ-9) score, remission, response, minimal clinically important difference (MCID) without response or remission, and documented adverse events at 28 days, 3 months, and 6 months. Propensity score matching was used for continuous follow-up of the PHQ-9 outcomes. Results: The analytic baseline cohort included 82 patients treated with intranasal esketamine-based therapy and 87 treated with venlafaxine-based therapy. The esketamine group had greater baseline depression severity and more previous antidepressant failures. At 3 months, no patients who continued treatment in either group met the remission criterion, one esketamine-treated patient achieved a response, and 37/61 (60.7%) esketamine-treated patients and 23/72 (31.9%) venlafaxine-treated patients achieved MCID without response or remission. At 6 months, remission remained absent; 27/61 (44.3%) esketamine-treated patients and 9/72 (12.5%) venlafaxine-treated patients met the response criterion, whereas 34/61 (55.7%) and 63/72 (87.5%) achieved MCID without response or remission, respectively. In propensity score-matched analyses, follow-up PHQ-9 scores were 1.02 points lower at 3 months (average treatment effect [ATE], −1.02; 95% CI, −1.70 to −0.35; p = 0.003) and 1.94 points lower at 6 months (ATE, −1.94; 95% CI, −3.17 to −0.71; p = 0.002) in the esketamine group than in the venlafaxine group. Dissociation and dizziness were documented more often in the esketamine group, whereas sexual dysfunction was documented more often in the venlafaxine group. Conclusions: In this retrospective routine care cohort, esketamine was used in patients with more complex TRD and was associated with modestly lower matched follow-up PHQ-9 scores. The observational design, baseline imbalance, and attrition precluded causal conclusions.